Innate Needs and Motivation : Self-Determination Theory in EFL Context - Elham Zarfsaz; Fahime Hosseini (International Journal of Practical and Pedagogical Issues in English Education)
This study attempted to investigate the Determination Theory in the Iranian EFL context by shedding light on the relationship between EFL learners’ basic psychological needs of autonomy, competence, and relatedness, and (intrinsic) motivation. To conduct the study, 324 Iranian EFL university students participated in the study. A standard questionnaire (on the students’ innate needs fulfillment and their second language motivation) developed by Agawa and Takeuchi (2016) was administered to the participants. Structural Equation Modeling (SEM) was employed to assess the proportion between hypothetical expectance and factual data. The model indicated that there was a substantial positive relationship between competence needs and Iranian EFL learners’ motivation. On the other hand, relatedness needs indicated a weaker influence on students’ motivation, and the autonomy needs fulfillment revealed to hold either negative or demotivating effects on Iranian L2 learners’ motivation.